Postoperative Admission of Adult Craniotomy Patients to the Neuroscience Ward Reduces Length of Stay and Cost. (18th November 2021) - Sun, Matthew Z; Babayan, Diana; Chen, Jia-Shu; Wang, Maxwell M; Naik, Priyanka K; Reitz, Kara; Li, Jingyi Jessica; Pouratian, Nader; Kim, Won
Graphical Abstract: